Functionality Analysis of Spent Coffee Ground Extracts Obtained by the Hydrothermal Method - Chin-Tung Wu; Dinesh Chandra Agrawal; Wen-Ying Huang; Hsiu-Cheng Hsu; Shang-Jhen Yang; Shu-Ling Huang; Yung-Sheng Lin (Journal of Chemistry)
Coffee is a popular beverage all over the world, but spent coffee grounds (SCGs) constituting almost 75% of original beans are usually considered waste and disposed off. The present study analyzed the functionalities of SCG with a view of its reuse in the cosmetic industry. The SCG extraction was carried out by the hydrothermal method. The resultant extracts were tested for its antioxidant capacity, tyrosinase inhibition, and moisturizing ability. LC–MS/MS results showed two major components in SCG extracts, namely, trigonelline and caffeine. Also, the SCG contained total flavonoid contents of 29 ± 4.5 mg quercetin equivalents (QE)/g SCG and total phenolic contents of 9.44 ± 0.90 mg gallic acid equivalents (GAE)/g SCG. Regarding functionality analysis, SCG extracts exhibited reduction capacity of 8.18 ± 0.39 mg vitamin C equivalent (VCE)/g SCG, DPPH free-radical scavenging activity (IC50) of 3.11 mg SCG/mL, ABTS free-radical scavenging activity (IC50) of 13.61 mg SCG/mL, and tyrosinase inhibition capacity (IC50) of 2.23 mg SCG/mL. Moreover, the volatilization rate of the extract solution (37 mg SCG/mL) reduced by 15.9%. These results demonstrate the utility of recycling of SCG and illustrate its potential application in the development of skin care products.